Dolomite-zirconia reaction sintered bonded coarse magnesia ceramics: Effect of the bonding proportion - Booth, Raul Fernando Nicolas (2021)
Refractory ceramic materials were manufactured, mainly composed of magnesia grains (coarse and medium fraction) and CaZrO3/MgO as a binding phase produced from the reaction sintering between CaMg(CO3)2(dolomite) and m-ZrO2 (monoclinic zirconia), which constituted the finer fraction. Different relationships between the proportion and the size of the different aggregates were studied. The microstructure of the materials was characterized in terms of density, crystalline phases, grain phase distribution, and morphology. A combination of X-ray diffraction analysis and scanning electron microscopy with microanalysis was used. The mechanical behavior was determined in terms of the room temperature dynamic Young's modulus and the 3-point bending modulus of rupture (MOR) at room temperature. All the materials remained with porosities above 30%. The microstructure developed was similar between the sintered materials, characterized with MgO coarse grains bonded by CaZrO3/c-ZrO2phases, and dispersed irregularly shaped pores. The MOR was directly related to the finer fraction content in the composition, where a higher quantity of finer fraction resulted in a higher MOR.